Myanmar Improving Public Financial Management for Health Services : Challenges and Opportunities for Improving Service Delivery in the Wake of COVID - World Bank (World Bank, Washington, DC, 2021)
Myanmar exhibits poor health outcomes and lags regional peers. Myanmar’s Human Capital Index (HCI) score is 0.47, compared to a regional average of 0.60. Every year, 2,000 pregnant women and 50,000 children die from preventable causes, and 29 percent of children under age 5 are stunted. While there are many reasons for these poor outcomes, the effective coverage (access, utilization, and quality) of service delivery in the health sector plays a fundamental role. Budget execution remains prominent among PFM challenges in the health sector, demonstrated by several roadblocks to spending on time and on target. There is an urgent need to better understand the PFM bottlenecks that affect frontline service delivery. Budgeted expenditure for the Ministry of Health and Sports (MoHS) has been increasing, but actual spending has been declining. Budgeted expenditure increased for the MoHS from 0.86 percent of gross domestic product (GDP) in 2014-15 to 1.15 percent of GDP in 2017-18. However, actual expenditure by MoHS has declined from 1.0 percent to 0.8 percent of GDP in the same period. The increase in resources available through the budget allocation process had helped expand access and availability of health services to some extent, but it has not been able to address significantly the major health challenges and achieve better outcomes at population level. This is partly due to weaknesses at several points along the chain of financial management within MoHS and at the point of service delivery. The main objective of this report on PFM in the health sector is to improve service delivery and the efficiency of health financing at all levels of health care in Myanmar. This will be achieved by identifying and analyzing relevant PFM bottlenecks and providing recommendations to address them. Secondary objectives are to deepen the understanding of PFM arrangements in Myanmar’s health sector, including the PFM reforms required under the health financing reforms for UHC, and strengthen the communication and coordination between MoHS and MOPFI to ensure sustainability of reforms going forward.